Aromaticity, Geometry and Charge Distribution of the N,N-Dimethylanthranilic Acid Conformers in Gas Phase - Irshaidat, Tareq (Asian Journal of Chemistry, 2011)
This computational organic chemistry study was performed using the hybrid functional B3LYP and the MP2 method. The study demonstrates that stabilizing conformer (I) by intramolecular hydrogen bonding causes distinguished electronic structure differences with respect to (II) and (III). To our best of knowledge and to the first time in the literature, the natural population analysis atomic charges allowed to estimate the amount of the delocalized charge and provided with evidence that the hydrogen bond in (I) can alter the σ bond polarization. Therefore, characteristics of this model amino acid are new addition to the hydrogen bond theory.